Looking forward to genetically edited fruit crops. Issue 2 (February 2015) - Nagamangala Kanchiswamy, Chidananda; Sargent, Daniel James; Velasco, Riccardo; Maffei, Massimo E.; Malnoy, Mickael
<x xml:space="preserve">Abstract</x> The availability of genome sequences for many fruit crops has redefined the boundaries of genetic engineering and genetically modified (GM) crop plants. However commercialization of GM crops is hindered by numerous regulatory and social hurdles. Here, we focus on recently developed genome-editing tools for fruit crop improvement and their importance from the consumer perspective. Challenges and opportunities for the deployment of new genome-editing tools for fruit plants are also discussed.